2011
DOI: 10.1038/nm.2307
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiles and the risk of developing diabetes

Abstract: Emerging technologies allow the high-throughput profiling of metabolic status from a blood specimen (metabolomics). We investigated whether metabolite profiles could predict the development of diabetes. Among 2,422 normoglycemic individuals followed for 12 years, 201 developed diabetes. Amino acids, amines, and other polar metabolites were profiled in baseline specimens using liquid chromatography-tandem mass spectrometry. Cases and controls were matched for age, body mass index and fasting glucose. Five branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

155
2,173
18
16

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,712 publications
(2,362 citation statements)
references
References 32 publications
155
2,173
18
16
Order By: Relevance
“…21 More specifically, metabolomics is a global and noninvasive analysis of biomarkers that are indicators of normal biological or pathogenic process, or response to therapeutic intervention, thereby helping to monitor treatment response. 22 Recent advances in metabolomics might provide various types of novel tumor markers for HCC.…”
Section: Metabolomic Features Of Hccmentioning
confidence: 99%
“…21 More specifically, metabolomics is a global and noninvasive analysis of biomarkers that are indicators of normal biological or pathogenic process, or response to therapeutic intervention, thereby helping to monitor treatment response. 22 Recent advances in metabolomics might provide various types of novel tumor markers for HCC.…”
Section: Metabolomic Features Of Hccmentioning
confidence: 99%
“…Glycerophospholipid and BCAA levels are reported to be related to insulin resistance, type 2 diabetes and obesity [29][30][31][32][33]. Moreover, population-based studies of previously healthy adults revealed that low lyso-PC C18:2 concentrations were associated with an increased risk of pre-type 2 diabetes and type 2 diabetes [30,34], while high concentrations of several diacyl-PCs (C32:1, C36:1, C38:3 and C40:5) were associated with a risk of type 2 diabetes independent of dietary, lifestyle and anthropometric factors.…”
Section: Discussionmentioning
confidence: 99%
“…It was envisaged from the point of discovery of pharmacometabonomics that the methodology would have this broader utility. [46] If the intervention is just passively the passage of time, the methodology can be used to predict disease onset in subsets of a population, and this has been demonstrated in several important cases, including the prediction of the onset of type-2 diabetes, [92][93][94] as well as in other diseases. [90] The power of metabolic profiling to provide prognosis of outcome in a wide variety of situations is one of the most exciting current aspects of this new science.…”
Section: Conclusion and The Future For Pharmacometabonomicsmentioning
confidence: 99%